Pengaruh Kunjungan Wisatawan terhadap Kesejahteraan Masyarakat - Muhammad Arfan Harahap; Anjur Perkasa Alam; Dian Permata Sari (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2020)
This study aims to analyze the influence of tourist visits on the welfare of the community around the tourism object (study on the community around the religious tourism object in Tuan Guru Besilam Babussalam Village). The source of this research data was obtained through a questionnaire given to the respondents. Processing and analysis of data in this study using SPSS 22.0 and Microsoft Office Excel. The results showed that tourist visits had a significant effect on the welfare of the community around the tourist attraction by 66%.